JCU 2017 Reviewers (Journal of Clinical Ultrasound, 2018)
Artery web is an uncommon intimal variant within the spectrum of fibromuscular dysplasia characterized by thin folds protruding into the arterial lumen, most commonly affecting the carotid arteries. Reports on lower-extremity artery webs are rare. This report presents a case of a deep femoral artery web in a 72-year-old woman. Ultrasound, contrast-enhanced ultrasound, and computed tomography angiography demonstrated a thin membrane-like intraluminal structure with localized flow disturbance but no hemodynamically significant stenosis or definite thrombus. Because the patient had no symptoms or signs of lower-extremity ischemia, she was managed conservatively. Ultrasound may provide a useful noninvasive method for detecting and monitoring artery webs in unusual vascular territories.